Designing interactive games for improving elementary school students’ number sense - Hermita, Neni; Alim, Jesi Alexander; Putra, Zetra Hainul; Gusti, Peggi Muharrani; Wijaya, Tommy Tanu; Pereira, Jerito (Al-Jabar: Jurnal Pendidikan Matematika, 2021)
Number sense is an essential primary mathematics material in elementary school that students must master. Learning media may be utilized in elementary schools' teaching and learning process to engage and inspire students to participate in learning activities, particularly mathematics. Therefore, the researchers designed an interactive game using Genially to improve students' number sense. The ADDIE development model was applied in the research and development procedure. In this research, the ADDIE development model began by analyzing problems related to the mathematics learning process in elementary schools, analyzing the environment and work situation, designing an interactive game, developing the game based on validation results from three media experts and two concept experts, and conducting a one-on-one trial. The product feasibility was tested on 46 students who were divided into two classes. Class B served as the experimental class, while Class A served as the control class. The interactive game's validation findings showed that the developed interactive learning media was practical and useful. As a result of the implementation, the experimental class students' grasp the material better than the control class.